AB0067 Influence of adipokines on differentiation of spongiosa-derived mesenchymal stromal cells from osteoporotic and osteoarthritis patients. (15th June 2017) - Tsiklauri, L; Neumann, E; Werner, J; Frommer, K; Engel, R; Rehart, S; Wenisch, S; Müller-Ladner, U
Abstract : Background: Osteoporosis (OP) and osteoarthritis (OA) are two common age-related disorders leading to chronic pain and disability in elderly people. Age-related bone loss and articular cartilage damage are associated with increased bone marrow adiposity due to a possible shift of osteogenic differentiation towards adipogenic differentiation of bone marrow mesenchymal stem cells (MSC). The differentiation of MSC into adipocytes or osteoblasts is an important determinant of bone structural integrity. Adipose tissue is an metabolically active tissue. Therefore adipocyte-derived factors -adipokines- might influence differentiation of bone marrow-derived MSC. Objectives: The role of fat-bone interactions in the pathogenesis of OP is poorly understood. Therefore, we analyzed the presence of distinct adipokines (visfatin, resistin and leptin) in the bone marrow cavity and their effects on MSC differentiation. Methods: Spongiosa from femoral heads was collected (hip replacement surgery of OA patients or after osteoporotic femoral neck fracture). MSC were cultured in adipogenic and osteogenic media with/without adipokines. For the transfer and differentiation of MSC on cancellous bone, bone fragments were purified and sterilized. mRNA expression of adipokines, bone marker genes, TIMPs and MMPs of stimulated MSC and bone samples were evaluated by realtime PCR. Matrix mineralization was assayed using Alizarin red S staining. Proinflammatory factors were measured by ELISA. Results: Visfatin and leptin levels were increased in OP bone vs. non-osteoporotic bone (n=14). In contrast to leptin and resistin, visfatin induced the secretion of proinflammatory factors (IL-6, IL-8, MCP-1) during both, osteogenic and adipogenic differentiation. Visfatin significantly increased the matrix mineralization and downregulated collagen type 1-expression (e.g. d21: -4.6-fold) in osteogenic differentiated cells. Visfatin also reduced the expression of MMP2, MMP13, RunX2, TIMP1 and TIMP2 (e.g. d21: -2.4-fold/-3.18-fold/-5.85-fold/-3.2-fold/-4.3 fold respectively) during osteogenic differentiation, but not leptin and resistin. In contrast to osteogenesis, visfatin significantly induced MMP13 expression (e.g. d21: 104-fold) during adipogenic differentiation under standard cell culture conditions. However, visfatin-induced MMP13-expression was markedly reduced during differentiation on purified autologous cancellous bone. Conclusions: Visfatin and leptin levels were elevated in osteoporotic bone tissue. Therefore, the visfatin-mediated increase of matrix mineralization and reduction of collagen type 1 expression might lead to enhanced bone fragility and contribute to the pathogenesis of OP. Visfatin induced release of proinflammatory cytokines and dysregulated expression of MMPs and TIMPs during osteogenic and adipogenic MSC-differentiation might influence bone turnover specifically at the adipose tissue/bone interface. Disclosure of Interest: None declared